Pengaruh Financial Distress, Leverage, dan Profitabilitas terhadap Konservatisme Akuntansi pada Perusahaan Menufaktur Subsektor Makanan dan Minuman - Ahmad Sarbani; Endang Asliana; Sahilly Dzulhasni (Jurnal Inovasi Ekonomi Syariah dan Akuntansi, 2025)
This study aims to see whether financial distress, leverage, and profitability affect accounting conservatism in manufacturing companies in the food and beverage subsector listed on the IDX for the 2021–2024 period. The independent variables used are financial distress, leverage, and profitability, while the bound variables are accounting conservatism. Data processing was carried out using the SPSS version 26 program with multiple linear regression methods. Sampling used purposive sampling techniques with certain criteria so that 63 companies were obtained as a sample for four years of observation (2021–2024). Of the total 252 financial statement data, after the deletion of outlier data, the number of data used became 183. The results of the study show that simultaneously financial distress, leverage, and profitability affect accounting conservatism. Partially, these three variables also have a positive effect on accounting conservatism. In addition, these findings indicate that companies with financial pressures and certain levels of financial management tend to apply higher prudential principles in the preparation of their financial statements.